Improved Dielectric, Magnetic, and Multiferroic Properties of (Bi0.5Na0.5)0.7La0.3(Ti0.7Fe0.3)O3 Ceramics Synthesis by the Solid-State Combustion Technique - Kornphom, Chittakorn; Somsri, Widchaya; Prasertpalichat, Sasipohn; Thatawong, Bhoowadol; Kruea-In, Chatchai; Udeye, Thanya; Rittidech, Aurawan; Menkun, Chanagon; Vittayakorn, Naratip; Pinitsoontorn, Supree; Jantaratana, Pongsakorn; Chanlek, Narong; et al. (My University, 2025)
Lead-free (Bi0.5Na0.5)0.7La0.3(Ti0.7Fe0.3)O3 ceramics (abbreviated as BNLTF) are synthesized by the solid-state combustion technique using glycine as fuel. The effect of the firing temperature (calcined between 700 and 800 °C for 2 h and sintered between at 800 and 900 °C for 2 h) on the phase structure, microstructure, electrical, and magnetic properties is investigated. Pure BNLTF powders are obtained with a calcination temperature of 750 °C for 2 h and the crystal size increases from 47 to 62 nm when the calcination temperature increases from 700 to 800 °C. All sintered BNLTF ceramics show a pure perovskite structure with a rhombohedral phase. The average grain size increases with increasing sintering temperatures. A well-packed microstructure with the highest density (5.98 g cm−3), good dielectric properties at room temperature (εr ≈ 589 and tanδ ≈ 0.572), soft ferroelectric behavior, and excellent magnetic properties (Ms ≈ 0.091 emu g−1, Mr ≈ 0.0026 emu g−1) is obtained from the ceramic sintered at 875 °C for 2 h. The multiferroic BNLTF ceramic sintered at 875 °C has a maximum magnetoelectric coupling coefficient (αE ≈ 2.08 mV cm−1 Oe−1) when the magnetic field is near 4500 Oe.
Keywords: (Bi0.5Na0.5)0.7La0.3(Ti0.7Fe0.3)O3 (BNLTF); combustion techniques; ferroelectric behaviors; magnetic properties; phase formations